Biodegradable nursing pad and preparation process thereof

By introducing a composite antibacterial hydrogel structure into the nursing pad, the shortcomings of the nursing pad in terms of rapid absorption, antibacterial properties and biodegradability are solved, achieving efficient absorption, continuous antibacterial protection and environmentally friendly biodegradability.

CN121667922AActive Publication Date: 2026-03-17GUANGZHOU JIANLANG MEDICAL TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610194620.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-11
Publication Date
2026-03-17
Estimated Expiration
2046-02-11

AI Technical Summary

Technical Problem

Existing nursing pads are inadequate in terms of rapid absorption, antibacterial properties, and biodegradability, posing a significant technical challenge in achieving highly efficient absorption, reliable antibacterial properties, and complete environmental degradability.

Method used

The product employs a composite antibacterial hydrogel structure, which integrates a composite antibacterial hydrogel and a fluff pulp fiber layer within an air-laid wood pulp fiber web. It is formed by cross-linking the fiber with a sodium alginate matrix and zinc ions using a silane coupling agent, combined with a skin-friendly top layer and an impermeable air-repellent bottom layer, creating a biodegradable nursing pad.

Benefits of technology

It achieves rapid absorption, continuous antibacterial protection, and environmental friendliness in nursing pads, improves moisture absorption and antibacterial properties, and ensures that the material degrades rapidly in the natural environment, reducing the environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of hygienic products, in particular to a biodegradable nursing pad and a preparation process thereof. The nursing pad comprises a skin-friendly top layer, a composite core absorption layer and an anti-seepage breathable bottom layer from top to bottom. The composite core absorption layer comprises a gel embedded framework and a fluff pulp fiber layer, wherein the gel embedded framework is composed of an air-laid wood pulp fiber net and composite antibacterial hydrogel which is cross-linked in situ and embedded in pores of the air-laid wood pulp fiber net, and the fluff pulp fiber layer is fixed to at least one surface of the framework. The composite antibacterial hydrogel comprises hydrophilic reinforced fibers modified by a silane coupling agent with hydrophilic groups, a sodium alginate matrix and zinc ions. The prepared nursing pad has excellent rapid absorption, efficient antibacterial and high biodegradability, and the problem that performance and environmental protection of a traditional product are difficult to consider at the same time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of sanitary products, in particular to a biodegradable nursing pad and a preparation process thereof. BACKGROUND

[0002] With the acceleration of the aging process of society and the general improvement of people's awareness of personal hygiene and nursing, the market demand for disposable sanitary products such as incontinence nursing pads and nursing pads for puerpera is growing. Traditional nursing pads usually adopt a multi-layer composite structure, aiming to achieve the core functions of rapid absorption, liquid locking and dry surface. However, the absorption core layer of most traditional nursing pads relies on a mixture of non-biodegradable high molecular water-absorbing resin and fluff pulp, and the outer layer often uses polypropylene non-woven fabric and polyethylene breathable film. Such polymer-based materials have a very long degradation period in the natural environment, and a large number of waste products have brought serious environmental pressure. Increasing environmental regulations and consumer expectations for sustainable products have made biodegradability of nursing pads an urgent demand.

[0003] At present, the industry has made many attempts to develop environmentally friendly nursing pads, such as using polylactic acid non-woven fabric, starch-based materials or increasing the amount of natural fibers. However, these improvements often face the problem of balancing performance and cost. On the one hand, the absorption core layer made of simply using or simply mixing biodegradable materials often has lower absorption rate, liquid holding capacity and anti-back seepage ability than traditional SAP composite materials, especially when dealing with a large amount of liquid discharge. On the other hand, the antibacterial agents introduced to improve functionality are mostly physical additives, which may have problems such as migration, precipitation or insufficient antibacterial durability, and some antibacterial ingredients may affect the biodegradation process or environmental compatibility of the material. Therefore, developing a nursing pad core structure that can achieve efficient absorption and reliable antibacterial function while ensuring that the overall material can be completely biodegraded after being discarded has become a prominent technical challenge in this field.

[0004] The prior art has not fully solved the three major problems of excellent use performance, long-term antibacterial hygiene and complete environmental degradability of disposable nursing pad products. There is an urgent need for a new solution in the market, which not only needs to implement the biodegradable concept in material selection, but also needs to prepare a high-performance absorption core that has fast liquid conduction, high capacity absorption and stable antibacterial function, and all components can be composted, so as to promote the substantial development of personal hygiene and nursing products towards the truly sustainable direction. SUMMARY

[0005] In view of the above problems in the prior art, the present application provides a biodegradable nursing pad and a preparation process thereof.

[0006] To solve the above technical problems, the technical scheme adopted by the present application is: A biodegradable nursing pad includes, from top to bottom, a skin-friendly top layer, a composite core absorbent layer, and an impermeable air bottom layer.

[0007] The composite core absorber layer includes: A gel-integrated framework, comprising an air-laid wood pulp fiber web and a composite antibacterial hydrogel formed in situ and embedded in its pores; and a fluff pulp fiber layer, the fluff pulp fiber layer being fixed to at least one surface of the gel-integrated framework by adhesive bonding or hot pressing. The composite antibacterial hydrogel comprises hydrophilic reinforcing fibers surface-modified with a silane coupling agent containing hydrophilic groups, a sodium alginate matrix, and zinc ions, and is formed by calcium ion crosslinking.

[0008] Traditional nursing pad materials, while offering some moisture absorption, often have weak antibacterial properties. Furthermore, the retained moisture after absorption can easily breed bacteria, leading to discomfort and odor. In contrast, composite antibacterial hydrogel not only enhances the moisture absorption of nursing pads, absorbing bodily fluids and moisture to keep skin dry, but also effectively inhibits bacterial growth during prolonged use, ensuring the hygiene and comfort of the pads. In addition, the addition of antibacterial components to the composite hydrogel extends the lifespan of the nursing pads, reduces the risk of bacterial transmission, and provides continuous antibacterial protection, especially in humid environments, ensuring its long-term effectiveness.

[0009] Preferably, in the gel-integrated skeleton, the dry basis mass ratio of the air-laid wood pulp fiber web to the composite antibacterial hydrogel is 1:(0.1-0.2); and the dry basis mass ratio of the fluff pulp fiber to the gel-integrated skeleton is (0.5-0.9):1.

[0010] Preferably, the method for preparing the composite antibacterial hydrogel is as follows: Preparation of a pre-gel composite aqueous phase of silane coupling agent modified hydrophilic reinforcing fiber, sodium alginate and zinc ions; The pre-gel composite aqueous phase is immersed in an air-laid wood pulp fiber web; The impregnated air-laid wood pulp fiber web is treated with a calcium ion crosslinking agent solution to cause sodium alginate to crosslink in situ within the pores of the skeleton, forming the composite antibacterial hydrogel.

[0011] This invention modifies the surface of hydrophilic reinforcing fibers by reacting them with a silane coupling agent, thereby enhancing the chemical reactivity of the fiber surface and strengthening its interfacial bonding with sodium alginate sol, thus improving the stability and mechanical properties of the composite material; Zn 2+ It coordinates / complexes with the carboxyl groups of sodium alginate and provides antibacterial activity; the final gel network is preferably composed of Ca. 2+Cross-linking and curing form a stable hydrogel structure, which also improves the stability of the gel and lays the foundation for subsequent composite reinforcement effects. The modified reinforcing fibers are combined with sodium alginate sol, and through stirring and high shear dispersion, the fibers are evenly distributed in the gel to form a fiber hydrogel composite system. This composite aqueous phase significantly improves the moisture absorption, antibacterial properties and biodegradability of the nursing pad.

[0012] Furthermore, the preparation method of the pre-gel composite aqueous phase includes: S1. Disperse 4.0-6.0g of hydrophilic reinforcing fiber in a mixed solvent of 140-200mL dimethylacetamide and 40-80mL water, and ultrasonically disperse for 20-60min at 50-60℃, 15-25kHz frequency, and 250-350W power to obtain a reinforcing fiber dispersion; dissolve 0.3-0.7g of silane coupling agent in 10-20mL of 20-40wt% ethanol aqueous solution, add the dispersion from step S1 while stirring at 300-500rpm, adjust the pH to 8.0-9.0 with ammonia, and continue ultrasonic treatment for 4-6h to obtain an organically modified reinforcing fiber dispersion; S2. Dissolve sodium alginate in water at a concentration of 2.0-3.0 wt%, and add zinc nitrate to make Zn 2+ The molar ratio of Zn to the carboxyl group in sodium alginate is (0.01-0.05):1, resulting in a product containing Zn. 2+ Sodium alginate sol; S3, Add 8-15 g of Zn-containing material from step S2. 2+ Sodium alginate sol was added to 10-20 g of organically modified reinforcing fiber dispersion from S1, stirred at 400-800 rpm for 10-40 min, and dispersed at 3000-6000 rpm under high shear for 1-5 min; the mixture was allowed to stand for 15-40 min to degas, and the pre-gel composite aqueous phase was obtained.

[0013] The hydrophilic reinforcing fiber includes at least one of sodium alginate fiber, chitosan fiber, and polyvinyl alcohol fiber; preferably, the hydrophilic reinforcing fiber is composed of sodium alginate fiber and chitosan fiber in a mass ratio of (1.2-1.8):1.

[0014] The composite antibacterial hydrogel of this invention mainly comprises sodium alginate sol and a modified reinforcing fiber dispersion, which interact to form a more uniform and stable composite system. After adding pre-gel composite water, the sodium alginate hydrogel binds more tightly to the reinforcing fibers, enabling in-situ cross-linking within the pores of the air-laid wood pulp fiber web to form a chimeric framework. This process not only effectively enhances the moisture absorption of the pad, allowing it to rapidly absorb and retain moisture, but also improves its antibacterial properties, ensuring that the antibacterial components are evenly distributed throughout the composite layer. Furthermore, the addition of pre-gel composite water significantly improves the biodegradability of the pad, as natural materials such as sodium alginate and chitosan possess excellent biodegradability, allowing the final pad to degrade more quickly in the natural environment, reducing environmental burden. Therefore, the addition of pre-gel composite water not only enhances the moisture absorption, antibacterial, and biodegradability of the pad but also ensures its stability and functionality during long-term use.

[0015] Preferably, the silane coupling agent comprises at least one of 3-[bis(2-hydroxyethyl)amino]propanetriethoxysilane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and N-[β-(N,N-diacetyl)aminoethyl]-γ-(N-acetyl)aminopropyltrimethoxysilane.

[0016] Preferably, the in-situ crosslinking steps are as follows: the pre-gel composite aqueous phase is uniformly impregnated into the air-laid wood pulp fiber web at 0.12-0.22 times the dry basis weight of the air-laid wood pulp fiber web, and then lightly pressed by rollers; subsequently, a calcium chloride solution with a concentration of 1.5-3.5 wt% is used for spray crosslinking, and the mixture is allowed to stand at 20-35℃ for 3-10 minutes to complete the crosslinking reaction.

[0017] Preferably, the skin-friendly top layer is polylactic acid spunbond nonwoven fabric, and the air-proof bottom layer is a hot water-soluble polyvinyl alcohol film.

[0018] A method for preparing a composite core absorber layer includes the following steps: The pre-gel composite aqueous phase is prepared using the method described above; the pre-gel composite aqueous phase is impregnated in an air-laid wood pulp fiber web; the impregnated air-laid wood pulp fiber web is cross-linked with calcium chloride solution to form a gel-chimera skeleton; fluff pulp fibers are laid on at least one surface of the gel-chimera skeleton and fixed by dot hot pressing or biodegradable hot melt adhesive dotting.

[0019] The conditions for the dotted hot pressing are: temperature 90-110℃, pressure 0.3-0.5 MPa, and time 0.5-2.0 s; the amount of the biodegradable hot melt adhesive applied is 1-3 g / m².

[0020] A process for preparing a biodegradable nursing pad includes the following steps: The skin-friendly top layer and the impermeable air-absorbing bottom layer are placed on the top and bottom of the composite core absorbent layer, respectively, and then hot-pressed together for 1-3 seconds at 80-120℃ and 0.3-0.7 MPa to obtain the nursing pad.

[0021] The application of the biodegradable nursing pad described above in the preparation of personal hygiene care products, including but not limited to incontinence care pads, maternity care pads, or pet care pads.

[0022] The beneficial effects of this invention are: 1. This invention provides a biodegradable nursing pad and its preparation process. By introducing a composite antibacterial hydrogel, the antibacterial components in the composite hydrogel provide continuous antibacterial protection for the nursing pad, preventing bacterial growth and reducing odor, thereby significantly improving the hygiene of the nursing pad. Simultaneously, the composite structure of hydrophilic reinforcing fibers and hydrogel significantly enhances the moisture absorption of the nursing pad, enabling it to absorb body fluids more quickly and effectively retain moisture while maintaining dryness for a longer period, avoiding discomfort caused by dampness, greatly improving the user's comfort experience, and effectively solving the problem of insufficient antibacterial performance in existing technologies.

[0023] 2. This invention uses natural fibers, which not only have good biodegradability but also can degrade rapidly in the natural environment, effectively reducing the burden on the environment and meeting the current needs of sustainable development.

[0024] 3. The preparation process of the composite core absorbent layer of this invention organically combines fiber modification, sol preparation, in-situ crosslinking, and interlayer composite. This process achieves uniform and robust composite of the hydrogel within the macroscopic fiber skeleton by controlling the composition, wetting amount, and crosslinking conditions of the gel precursor. The fixation method of dot-matrix hot pressing or biodegradable hot melt adhesive application ensures interlayer bonding while maximizing the material's softness and breathability. The entire process is highly controllable, suitable for large-scale production, and ensures the stability and efficiency of the nursing pad's production. Detailed Implementation

[0025] The invention will now be described in further detail with reference to specific embodiments, but it should not be construed as limiting the scope of the invention to the following embodiments.

[0026] The raw materials described in this application are partially described; all other raw materials not described are commercially available. PLA spunbond nonwoven fabric was purchased from Wenzhou Chaocheng Nonwoven Technology Co., Ltd., with a basis weight of 80 g / m². 2 .

[0027] Hot water soluble polyvinyl alcohol films are prepared by conventional methods: they are made from fully alcoholyzed polyvinyl alcohol through solution coating and drying or melt blown film process, followed by recrystallization. The film has a solubility temperature in water between 80-100℃ and a thickness between 10-50μm.

[0028] Chitosan fiber was purchased from Qingdao Jifa New Materials Co., Ltd., with a basis weight of 40-70 g / m². 2 .

[0029] The polyvinyl alcohol fiber was purchased from Taian Yilin New Materials Co., Ltd., with a length of 40mm and a diameter of 15μm.

[0030] Example 1 A biodegradable nursing pad comprises, from top to bottom, a skin-friendly top layer, a composite core absorbent layer, and an impermeable air-absorbing bottom layer. The skin-friendly top layer is a biodegradable, skin-friendly non-woven fabric with a thickness of 0.2 mm; the composite core absorbent layer is a laminated absorbent diffusion layer comprising an air-laid wood pulp fiber web, a composite antibacterial hydrogel, and a fluffy pulp fiber layer formed on the upper and / or lower surfaces; the impermeable air-absorbing bottom layer is made of a hot-water soluble polyvinyl alcohol film with a thickness of 0.04 mm.

[0031] The biodegradable, skin-friendly nonwoven fabric is PLA spunbond nonwoven fabric.

[0032] The raw materials of the composite core absorbent layer include: air-laid wood pulp fiber web, composite antibacterial hydrogel, and fluff pulp fiber, with a dry basis mass ratio of 1:0.15:0.7.

[0033] The preparation method of the composite antibacterial hydrogel is as follows: S1. 4.8 g of hydrophilic reinforcing fiber was dispersed in a mixed solution of 140 mL dimethylacetamide and 60 mL ethanol, and ultrasonically dispersed at 55 °C, ultrasonic frequency 20 kHz, and power 300 W for 30 min to obtain a reinforcing fiber dispersion. 0.5 g of silane coupling agent was dissolved in 15 mL of 30 wt% ethanol aqueous solution and added to the reinforcing fiber dispersion while stirring at 400 rpm. The pH of the solution was adjusted to 8.5 with 25 wt% ammonia water, and ultrasonication was continued for 5 h to obtain an organically modified reinforcing fiber dispersion. The hydrophilic reinforcing fiber was composed of sodium alginate fiber and chitosan fiber in a mass ratio of 3:2. The silane coupling agent was 3-[bis(2-hydroxyethyl)amino]propanetriethoxysilane. S2. Weigh 2.5 g of sodium alginate and add it to 97.5 mL of water. Stir at 500 rpm for 2 h at room temperature to obtain a sodium alginate solution. Add 0.1 g of zinc nitrate and continue stirring for 20 min to obtain a solution containing Zn. 2+ Sodium alginate sol; S3. Take 10 g of the Zn-containing sample obtained in step S2.2+ Sodium alginate sol was added to 12 g of organically modified reinforcing fiber dispersion from S1, and stirred at 600 rpm for 15 min; then dispersed at 4000 rpm under high shear for 2 min; and allowed to stand for degassing for 20 min to obtain the pre-gel composite aqueous phase. S4. Prepare a 2.0 wt% calcium chloride solution and stir to dissolve it for later use. Cut the air-laid wood pulp fiber mesh into 80cm×90cm pieces. According to the ratio of air-laid wood pulp fiber mesh: gel (dry basis) = 1:0.15, uniformly impregnate the pre-gel composite aqueous phase obtained in step S3 into the air-laid wood pulp fiber mesh, and lightly press it once with a pressure roller to allow the sol to enter the pores of the skeleton. Then, uniformly spray the above 2.0 wt% calcium chloride solution on both sides of the impregnated air-laid wood pulp fiber mesh, and let it stand at 25°C for 5 minutes to complete the cross-linking, so that sodium alginate forms a composite antibacterial hydrogel in situ in the pores of the skeleton, and obtain a gel-embedded air-laid support skeleton.

[0034] The composite core absorbent layer is prepared as follows: The gel-embedded air-web support skeleton obtained in step S4 is prepared with a dry basis mass ratio of 1:0.7 to the fluff pulp fiber. The fluff pulp fiber is evenly spread on the upper and / or lower surface of the support skeleton and pressed once with a light pressure roller to firmly bond the fluff pulp fiber to the hydrogel layer and the surface of the support skeleton. Subsequently, it is fixed by dot hot pressing or dot coating with biodegradable hot melt adhesive to obtain the composite core absorbent layer.

[0035] The dot-matrix hot-pressing conditions were: temperature 100℃, pressure 0.4MPa, and time 1.0 s; the amount of biodegradable hot melt adhesive applied was 2 g / m³. 2 .

[0036] The preparation process of the biodegradable nursing pad is as follows: the skin-friendly top layer and the impermeable air bottom layer are placed on the top and bottom of the composite core absorbent layer, respectively, and hot-pressed together for 2 seconds under the conditions of 100℃ and 0.5MPa pressure to obtain the biodegradable nursing pad.

[0037] Example 2 The method is basically the same as Example 1, except that the hydrophilic reinforcing fiber in S1 of the preparation method of the composite antibacterial hydrogel is sodium alginate fiber, which is obtained by mechanically cutting sodium alginate to a length of 10 mm.

[0038] Example 3 It is basically the same as Example 1, except that the hydrophilic reinforcing fiber in S1 of the preparation method of the composite antibacterial hydrogel is chitosan fiber.

[0039] Example 4 It is basically the same as Example 1, except that the hydrophilic reinforcing fiber in S1 of the preparation method of the composite antibacterial hydrogel is polyvinyl alcohol fiber.

[0040] Example 5 The method is basically the same as Example 1, except that the silane coupling agent in S1 of the preparation method of the composite antibacterial hydrogel is 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane.

[0041] Example 6 The method is basically the same as Example 1, except that the silane coupling agent in S1 of the preparation method of the composite antibacterial hydrogel is N-[β-(N,N-diacetyl)aminoethyl]-γ-(N-acetyl)aminopropyltrimethoxysilane.

[0042] Comparative Example 1 The method is basically the same as Example 1, except that the silane coupling agent in S1 of the preparation method of the composite antibacterial hydrogel is hexadecyltriethoxysilane, a silane coupling agent without hydrophilic groups.

[0043] Comparative Example 2 The method is basically the same as that in Example 1, except that in the preparation method of the composite antibacterial hydrogel, silane coupling agent is not used for modification in S1.

[0044] The preparation method of the composite antibacterial hydrogel is as follows: S1. Disperse 4.8g of hydrophilic reinforcing fiber in a mixed solution of 140mL dimethylacetamide and 60mL ethanol, and sonicate at 55℃, ultrasonic frequency 20 kHz and power 300 W for 30min to obtain a reinforcing fiber dispersion. S2. Weigh 2.5 g of sodium alginate and add it to 97.5 mL of water. Stir at 500 rpm for 2 h at room temperature to obtain a sodium alginate solution. Add 0.1 g of zinc nitrate and continue stirring for 20 min to obtain a solution containing Zn. 2+ Sodium alginate sol; S3. Take 10 g of the Zn-containing sample obtained in step S2. 2+ Sodium alginate sol was added to 12 g of the reinforcing fiber dispersion in S1 and stirred at 600 rpm for 15 min; then dispersed at 4000 rpm under high shear for 2 min; and allowed to stand for 20 min to degas, to obtain the pre-gel composite aqueous phase. S4. Prepare a 2.0 wt% calcium chloride solution and stir to dissolve it for later use. Cut the air-laid wood pulp fiber mesh into 80cm×90cm pieces. According to the ratio of air-laid wood pulp fiber mesh: gel (dry basis) = 1:0.15, uniformly impregnate the pre-gel composite aqueous phase obtained in step S3 into the air-laid wood pulp fiber mesh, and lightly press it once with a pressure roller to allow the sol to enter the pores of the skeleton. Then, uniformly spray the above 2.0 wt% calcium chloride solution on both sides of the impregnated air-laid wood pulp fiber mesh, and let it stand at 25°C for 5 minutes to complete the cross-linking, so that sodium alginate forms a composite antibacterial hydrogel in situ in the pores of the skeleton, and obtain a gel-embedded air-laid support skeleton.

[0045] Comparative Example 3 The method is basically the same as that in Example 1, except that the hydrophilic reinforcing fiber in S1 of the preparation method of the composite antibacterial hydrogel is composed of sodium alginate fiber and polypropylene fiber in a mass ratio of 3:2.

[0046] Comparative Example 4 The method is basically the same as in Example 1, except that the reinforcing fiber in S1 of the preparation method of the composite antibacterial hydrogel is a conventional hydrophilic polypropylene fiber.

[0047] Test Example 1 Determination of moisture absorption performance: The nursing pads prepared in the above examples and comparative examples were tested according to the method in the national standard GB / T21655.1-2023 "Evaluation of moisture absorption and quick-drying properties of textiles - Part 1: Single combination test method". The test samples were cut according to the required size of the nursing pad (600mm×600mm). 300mL of fresh urine was added to the nursing pad test sample at a urine addition rate of 300ml per minute. The time required for complete absorption (min) was recorded. The absorption time was tested. Each group was tested 5 times and the average value was taken. The results are shown in Table 1.

[0048] Antibacterial performance test: The nursing pads prepared in the above examples and comparative examples were tested according to the national standard GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles - Part 3: Vibration method". 0.5g of sample was mixed with 5mL of bacterial suspension (Staphylococcus aureus, concentration 1×10⁻⁶). 5 After shaking and contacting the solution in an Erlenmeyer flask (CFU / mL) for 1 hour, collect the solution for viable bacteria counting.

[0049] Antibacterial rate (%) = (AB) / A × 100%; where A is the average colony count of the blank sample and B is the average colony count of the sample. Each group was tested 3 times and the average value was taken. The results are shown in Table 1.

[0050] Table 1. Tests of moisture absorption and antibacterial properties

[0051] Test Example 2 Biodegradation rate: Referring to the national standard GB / T19277.1-2025 "Determination of the final aerobic biodegradability of materials under controlled composting conditions—Method for determining the release of carbon dioxide—Part 1: General Method", the aerobic biodegradability of the nursing pads prepared in the above examples and comparative examples was tested using the composting method. At 58℃, the carbon dioxide release of the samples was measured over 90 days, and its percentage relative to the theoretical carbon dioxide production was calculated. Each sample was tested three times, and the average value was taken. The results are shown in Table 2.

[0052] Table 2 Biodegradability Performance Test

[0053] The nursing pad prepared by this invention exhibits excellent moisture absorption, antibacterial properties, and biodegradability. Specific analysis is as follows: The moisture absorption time of Examples 1 to 6 is significantly lower than that of Comparative Examples 1 to 4. In particular, Example 1 has a moisture absorption time of only 2.4 min, far lower than the 7.8 min of Comparative Example 1. The main reason is the composite structure of the antibacterial hydrogel and hydrophilic reinforcing fibers, which significantly improves the moisture absorption rate and moisture retention capacity of the nursing pad. In contrast, the hydrogel and fiber composite in the traditional control group exhibits poor moisture absorption performance.

[0054] The antibacterial performance test results showed that the antibacterial rate of Example 1 was as high as 99.8%, significantly higher than the antibacterial rates of Comparative Example 1 (86.7%) and Comparative Example 3 (71.6%). This difference is due to the composite antibacterial hydrogel used in this invention, which not only utilizes hydrophilic reinforcing fibers modified with a silane coupling agent but also introduces zinc ions with antibacterial effects, effectively enhancing the antibacterial performance of the pad. In the control group, the reinforcing fibers without surface modification or the use of more traditional antibacterial treatment methods resulted in weaker antibacterial effects.

[0055] Biodegradability test results showed that Example 1 had a degradation rate of 97.2%, significantly better than the control group. This indicates that the combination of natural fibers and composite antibacterial hydrogel used in this invention ensures faster degradation of the pad in the natural environment, reducing environmental burden. In contrast, traditional technologies using polymer materials or non-degradable components result in weaker degradation capabilities and lower degradation rates.

Claims

1. A biodegradable care pad characterized in that, The skin-friendly top layer, the composite core absorption layer, and the gas-impermeable bottom layer are sequentially arranged from top to bottom. The composite core absorption layer comprises: A gel-embedded skeleton composed of an air-laid wood pulp fiber web and a composite antibacterial hydrogel formed in situ and embedded in the pores thereof, and a fluff pulp fiber layer fixed to at least one surface of the gel-embedded skeleton by adhesion or hot pressing; The composite antibacterial hydrogel comprises hydrophilic reinforcing fibers surface-modified by a silane coupling agent, a sodium alginate matrix, and zinc ions, and is formed by cross-linking with calcium ions.

2. The biodegradable nursing pad of claim 1, wherein, The hydrophilic reinforcing fibers include at least one of sodium alginate fibers, chitosan fibers, and polyvinyl alcohol fibers.

3. The biodegradable nursing pad of claim 1, wherein, In the gel-embedded skeleton, the dry basis mass ratio of the air-laid wood pulp fiber web to the composite antibacterial hydrogel is 1:(0.1-0.2); and the dry basis mass ratio of the fluff pulp fiber to the gel-embedded skeleton is (0.5-0.9):

1. The preparation method of the composite antibacterial hydrogel is as follows: A gel precursor composite aqueous phase of the silane coupling agent-modified hydrophilic reinforcing fibers, sodium alginate, and zinc ions is prepared; The gel precursor composite aqueous phase is infiltrated into the air-laid wood pulp fiber web; 4. The biodegradable nursing pad of claim 3, wherein, The air-laid wood pulp fiber web after infiltration is treated with a calcium ion cross-linking agent solution to cross-link the sodium alginate in situ in the pores of the skeleton, forming the composite antibacterial hydrogel. The preparation method of the gel precursor composite aqueous phase comprises: S2, dissolve sodium alginate in water at a concentration of 2.0-3.0 wt%, and add zinc nitrate so that the molar ratio of Zn 2+ to the carboxyl group in sodium alginate is (0.01-0.05): 1 to obtain a sodium alginate sol containing Zn 2+ . S3. Add 8-15 g of the sodium alginate sol of step S2 containing Zn 2+ of step S1 under stirring at 400-800 rpm for 10-40 min, followed by high shear dispersion and standing to de-aerate, to obtain the gel precursor composite aqueous phase.

5. The biodegradable nursing pad of claim 3, wherein, S1. 4.0-6.0 g of hydrophilic reinforcing fibers are dispersed in 140-200 mL of a mixed solvent of dimethylacetamide and 40-80 mL of water, ultrasonic dispersion is performed at 50-60°C, a frequency of 15-25 kHz, and a power of 250-350 W for 20-60 min to obtain a reinforcing fiber dispersion liquid; 0.3-0.7 g of a silane coupling agent is dissolved in 10-20 mL of a 30 wt% ethanol aqueous solution, added to the dispersion liquid of step S1 under stirring at 300-500 rpm, and adjusted to a pH of 8.0-9.0 with ammonia water, and then ultrasonic treatment is continued for 4-6 h to obtain an organic modified reinforcing fiber dispersion liquid; 6. The biodegradable nursing pad of claim 1, wherein, The in-situ cross-linking specifically comprises: the gel precursor composite aqueous phase is uniformly infiltrated into the air-laid wood pulp fiber web at 0.12-0.22 times the dry basis mass of the air-laid wood pulp fiber web, and light roller pressing is performed; then a calcium chloride solution with a concentration of 1.5-3.5 wt% is used for spraying cross-linking, and the cross-linking reaction is completed after standing at 20-35°C for 3-10 min.

7. A method of making a composite wicking absorbent layer, characterized by, The skin-friendly top layer is a polylactic acid spun-bonded non-woven fabric, and the gas-impermeable bottom layer is a hot water-soluble polyvinyl alcohol film. The method comprises the following steps: The gel precursor composite aqueous phase obtained by the preparation method of the composite antibacterial hydrogel according to claim 3 is used; the gel precursor composite aqueous phase is infiltrated into the air-laid wood pulp fiber web; and the air-laid wood pulp fiber web after infiltration is cross-linked with a calcium chloride solution to form a gel-embedded skeleton; Fluff pulp fibers are laid on at least one surface of the gel-embedded skeleton and fixed by point hot pressing or degradable hot melt adhesive point coating.

8. The preparation method according to claim 7, characterized in that, The point-like hot pressing condition is: temperature 90-110℃, pressure 0.3-0.5 MPa, time 0.5-2.0 s; the degradable hot melt adhesive point coating amount is 1-3 g / m².

9. A process for the preparation of a biodegradable care pad, characterized in that, The method comprises the following steps: placing a skin-friendly top layer and an air impermeable bottom layer on the top and bottom of a composite core absorption layer respectively, and hot pressing the composite under the condition of 80-120℃ and 0.3-0.7 MPa for 1-3 s to obtain the nursing pad.

10. Use of the biodegradable nursing pad according to claim 1 in the preparation of personal hygiene care products, including but not limited to incontinence nursing pads, nursing pads for puerpera or pet nursing pads.

Citation Information

Patent Citations

  • Antibacterial high-water-absorption linen and preparation method thereof

    CN108729214A

  • Traditional Chinese medicine privacy nursing plaster and preparation method thereof

    CN110917178A

  • Nursing pad for emergency department

    CN212395208U

  • Absorbent structures with gelling agent and absorbent articles containing such structures

    US5061259A